Acute and chronic effects of cortisol on milk yield, the expression of key receptors, and apoptosis of mammary epithelial cells in Saanen goats - G.F. Bomfim; G.K.F. Merighe; S.A. de Oliveira; J.A. Negrao (Journal of Dairy Science, 2022)
ABSTRACT: Cortisol (CORT) induces mammary development in late gestation and is fundamental to the differentiation of mammary epithelial cells and lactogenesis. The objective of this study was to investigate the relationship between CORT, insulin, prolactin, growth hormone, and insulin-like growth factor-1 in milk as well as the effect of CORT on the expression of receptors of insulin (INSR), prolactin (PRLR), growth hormone (GHR); we also studied the insulin-like growth factor-1 (IGF1R), glucocorticoid (NR3C1), mineralocorticoid (NR3C2), B-cell lymphoma 2 (BCL2), BCL-2-like protein X (BAX) genes, and the apoptosis rate of mammary epithelial cells of lactating Saanen goats in vivo and in vitro. The following experiments were conducted: (1) comparing hormone release in milk and blood after ACTH or a placebo administration; (2) evaluating the effect of acute CORT increases in mammary gland expression and milk yield in vivo; and (3) evaluating the effect of a chronic increase in CORT concentration in epithelial mammary cell apoptosis in vitro. In vivo, ACTH administration significantly increased CORT release but did not affect insulin, prolactin, growth hormone, and insulin-like growth factor-1 release in plasma and milk versus placebo. The results show also that a low CORT release after ACTH administration increased the expression of GHR and PRLR genes in the mammary tissue. Indeed, CORT release significantly increased the milk yield from goats subjected to ACTH versus goats subjected to the placebo. However, a higher amount of CORT added in vitro upregulated the NR3C1, GHR, PRLR, and BAX genes and downregulated the IGF1R and INSR genes, which could negatively modulate the apoptosis of mammary epithelial cells. Finally, the effect of CORT in vivo after ACTH administration demonstrated the increased expression of the PRLR and GHR genes, which may improve epithelial cell responsiveness and be associated with the positive effect of CORT observed on milk yield at mid-end lactation.